Caracterización fincas agroecológicas del departamento del Meta, Colombia - Zárate Lozada, Juan Pablo (2025)
The global food system is increasingly constrained by environmental degradation and biodiversity loss, leading to drastic climate changes and exacerbating rural poverty. In response, the Sustainable Development Goals (SDGs), framed within the 2030 Agenda, aim to establish a transformative vision toward sustainability, both for and from the territories. Within this context, agroecology faces multiple challenges in promoting food security and sovereignty. Knowledge Gap: There is a significant lack of statistical and descriptive information, from both quantitative and qualitative perspectives, regarding agroecological farms in the Meta department. This underscores the necessity for future research to register such data at the regional level to provide insights into the challenges and opportunities associated with the adoption of agroecological practices. Purpose: The primary objective of this research is to characterize the farms in the department that implement agroecology as a production methodology, aiming to conduct a comprehensive analysis of the socio-environmental and economic dynamics. This will yield information for subsequent interpretation, with the goal of understanding the complexity and integrative approach of these systems. Methodology: The research employs a non-experimental, cross-sectional methodology to characterize agroecological practices and production system management in nine farms within the Meta department. These farms, located in the subregions of Ariari, the Cordillera, Altillanura, and the Capital Cordillera, were previously identified and recognized for their sustainable activities. A statistical analysis was conducted through surveys based on indicators such as productivity, diversity, water resources, as well as a deep understanding of subjective aspects like the producers' perceptions, educational level, and commercialization practices. Results and Conclusions: The studied agroecological farms exhibit diversity, with no common crop observed across the farms, in their production and management, highlighting the importance of conserving natural resources, adopting sustainable technologies, direct consumer marketing through local markets, and the combination of traditional knowledge with technical advice. These factors contribute to promoting sustainability and food security within their communities.